2018
DOI: 10.1021/acssensors.7b00894
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Construction of Protein-Based Semisynthetic Biosensors

Abstract: Chemically constructed biosensors consisting of a protein scaffold and an artificial small molecule have recently been recognized as attractive analytical tools for the specific detection and real-time monitoring of various biological substances or events in cells. Conventionally, such semisynthetic biosensors have been prepared in test tubes and then introduced into cells using invasive methods. With the impressive advances seen in bioorthogonal protein conjugation methodologies, however, it is now becoming f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 136 publications
(221 reference statements)
0
17
0
Order By: Relevance
“…If proteins, such as antibodies, are used as the recognition unit, the design of a probe on the basis of the AIE is possible, but needs careful evaluation and much effort . Shi and co‐workers developed a cetuximab–AIEgen conjugate (mAb‐CSPP) to target EGFR protein marker overexpressed on the membrane of cancer cells (Table , entry 15) .…”
Section: Detection Localization and Quantification Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…If proteins, such as antibodies, are used as the recognition unit, the design of a probe on the basis of the AIE is possible, but needs careful evaluation and much effort . Shi and co‐workers developed a cetuximab–AIEgen conjugate (mAb‐CSPP) to target EGFR protein marker overexpressed on the membrane of cancer cells (Table , entry 15) .…”
Section: Detection Localization and Quantification Of Proteinsmentioning
confidence: 99%
“…If proteins, such as antibodies, are used as the recognition unit, the design of ap robe on the basis of the AIE is possible, but needs careful evaluation and much effort. [63] Shi and coworkers developed ac etuximab-AIEgen conjugate (mAb-CSPP) to target EGFR protein marker overexpressed on the membrane of cancerc ells (Table 1, entry 15). [52] Under living conditions, the probe was, however,n ot able to light up the protein (even if the probe-target interactions had been confirmed by other methods);t his was likely to be attributed to insufficient RIM effects on the dye as ar esult of protein-protein binding.I f mounting mediumw as used to "solidify" the sample additionally,t he desired signals thus reached significant levels.…”
Section: Microscopic Visualization Of Proteins In Biological Systemsmentioning
confidence: 99%
“…It has been demonstrated that LD and AG chemistries are applicable for visualization of endogenous proteins, 211,215,217,218 biosensor construction, 11,12,[219][220][221] protein-protein interaction analyses, [222][223][224] design of a new type of covalent inhibitor 199 and drug screening in live cell environments. 221 For example, Hamachi, Kiyonaka and coworkers recently demonstrated that fluorophore-labeled AMPA-type glutamate receptors (AMPARs) prepared by LDAI chemistry act as turn-on-type fluorescent biosensors for AMPAR ligands under live cell conditions.…”
Section: •3 Chemical Labeling Using Affinity-guided Catalystsmentioning
confidence: 99%
“…6,7 The conjugation of monoclonal antibodies with cytotoxic compounds directed to tumor cells has emerged as a strategy for generating highly potent biopharmaceutical drugs (antibody-drug conjugates, ADCs). [8][9][10] Moreover, proteins chemically modified with a fluorophore or artificial functionalities have been applied to construct biosensors, [11][12][13] engineer biocatalysts, 14 and protein-based biomaterials. 15 In most cases, selectivity is one of the key issues in chemical modification of proteins (in terms of amino acid selectivity, site selectivity, number of modification sites and protein selectivity).…”
Section: Introductionmentioning
confidence: 99%
“…There are a range of fluorophores that can be added directly to cells to discern cell function and behavior (9) including molecules that respond to pH (10) and redox state (11). However, these molecules tend to be cleared rapidly from cells, especially retinal cells (12).…”
Section: Introductionmentioning
confidence: 99%